Nurses’ knowledge on the classification, prevalence and consequences of arterial hypertension - Grabowska, Hanna; Grabowski, Władysław; Świetlik, Dariusz; Narkiewicz, Krzysztof (Polish Journal of Public Health, 2013)
Introduction. Arterial hypertension, the prevalence of which in the adult population of developed countries varies from 20-50%, is one of the most significant risk factors of cardiovascular disorders, being the principal cause of mortality in Europe and leading to a deterioration in the quality of life and to disability. Aim. The purpose of this study was to assess nurses’ knowledge on the current classification of BP levels and hypertension as well as of its prevalence and clinical consequences. Material and methods. The study included 1,108 participants (W-1,089, M-19, aged 21-60, 0-37 years of work experience). The study was conducted in 2007-2009 using the diagnostic survey method. Results. Half of the respondents correctly defined the prevalence of arterial hypertension in Poland and indicated the levels of optimal blood pressure and the arterial hypertension threshold. The best-known consequences of hypertension were stroke (93.5%), coronary heart disease (86.1%) and heart failure (84.6%). Sex, place of residence, length of service, holding a Bachelor’s diploma and completion of specialization training were not found to significantly affect the respondents’ answers. Significantly more correct answers were given by respondents aged 20-25 who had not started to work yet, those who were not married, and graduates from master’s degree studies in nursing. Conclusions. The study subjects demonstrated a moderate level of knowledge of the prevalence rate, classification of BP levels and diagnostic criteria for arterial hypertension, and an acceptable level of knowledge of hypertension complications.